Mucociliary system of the respiratory tract in children with asthma and allergic rhinitis - I. V. Ozerskaya; N. A. Geppe; U. S. Malyavina; G. Chakroborti (Сеченовский вестник, 2014)
Mucociliary system disturbances play a significant role in the pathogenesis of bronchopulmonary diseases. Preliminary results of our research concerning mucosiliary system functioning in children with asthma and allergic rhinitis are listed. Digital videocomplex was used to assess functioning of nasal ciliary epithelium. Our data suggest signifi cant structural and functional abnormalities of ciliary epithelium in asthma and allergic rhinitis.